Studies on the incidence of droughts through seasonal aridity index - SARMA , AALN; RAVINDRANATH, M (MAUSAM, 1986)
An attempt has been made in the present study to evolve the aridity index (lsa) for the southwest monsoon season through water balance concept. Madras and Masulipatnam have been selected to study the occurrence of droughts during the period 1901-1975. A scheme is suggested for drought categorization. A critical appraisal is made in choosing the seasonal aridity index compared to annuals.